2017
DOI: 10.1080/00275514.2017.1303861
|View full text |Cite
|
Sign up to set email alerts
|

Geosmithiaassociated with bark beetles and woodborers in the western USA: taxonomic diversity and vector specificity

Abstract: Fungi in the genus Geosmithia (Ascomycota: Hypocreales) are frequent associates of bark beetles and woodborers that colonize hardwood and coniferous trees. One species, Geosmithia morbida, is an economically damaging invasive species. The authors surveyed the Geosmithia species of California and Colorado, USA, to (i) provide baseline data on taxonomy of Geosmithia and beetle vector specificity across the western USA; (ii) investigate the subcortical beetle fauna for alternative vectors of the invasive G. morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 67 publications
6
63
1
Order By: Relevance
“…The European silver fir weevil (P. piceae) and the striped ambrosia beetle (T. lineatum) were not associated with Geosmithia in our study. Similar results have recently been reported from the Western USA [11]. According to a study conducted by Kolařík et al [11], Geosmithia spp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The European silver fir weevil (P. piceae) and the striped ambrosia beetle (T. lineatum) were not associated with Geosmithia in our study. Similar results have recently been reported from the Western USA [11]. According to a study conducted by Kolařík et al [11], Geosmithia spp.…”
Section: Discussionsupporting
confidence: 90%
“…where adults do not enter these tissues. Although, there are many studies confirming associations between ambrosia beetles and Geosmithia fungi [8,10,11,14,16], our study showed that T. lineatum does not transmit Geosmithia. There was also no evidence that this ambrosia beetle can transmit Geosmithia fungi in pine habitats [9].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We were unable to devise a primer pair using the ITS region that was specific enough to detect G. morbida alone (unpublished results). This is consistent with other researchers' observations that the ITS region is not sufficiently informative to distinguish certain Geosmithia species (Kolařík et al 2017). An 86% accuracy level for detection of G. morbida was determined for this protocol based on DNA sequencing results.…”
Section: Implications and Conclusionsupporting
confidence: 89%
“…Pityophthorus juglandis (Bright, 1981) and G. morbida (Kolařík et al, 2011; Tisserat et al, 2011) were first collected and described from populations in the western USA, and since 2010, they have also spread to the eastern USA (Seybold et al, 2013a, 2016). Surveys in the western USA suggest that P. juglandis may be the only subcortical insect to carry G. morbida (Kolařík et al, 2017). There have been reports from the eastern USA that other subcortical insects may vector G. morbida in walnut, but the phoresy rates have been low, transmission has not been demonstrated experimentally, and the insects were mostly species that target moribund trees (Juzwik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%